Critical seasonal conditions in the reindeer-herding year: A synopsis of factors and events in Fennoscandia and northwestern Russia - Laptander, Roza; Horstkotte, Tim; Habeck, Joachim Otto; Rasmus, Sirpa; Komu, Teresa; Matthes, Heidrun; Tømmervik, Hans; Istomin, Kirill; Eronen, Jussi T.; Forbes, Bruce C. (Polar science, 2024)
In this article, we identify what herders in Fennoscandia and northwestern Russia see as critical conditions and events in the annual reindeer herding cycle. Indigenous Sámi and Yamal reindeer herders identify eight seasons, each of which has crucial importance in its own way. Differences in perception between Fennoscandian and northwestern Russian reindeer herders about good and bad seasonal conditions are based on the degree of climatic and geographic variation, herd control and the variety of simultaneous pressures on pastures. The scope and speed of ongoing climate change in the Arctic will profoundly modify these conditions, and consequently shape critical events and outcomes in reindeer herding. The resulting challenges need to be assessed in the context of social and economic dynamics. Reindeer herders throughout Fennoscandia and Russia are concerned about future prospects of their livelihood. To adapt to climate change and develop new strategies, reindeer herders must have access to pastures; they must retain their mobility and flexibility; and their participation in land-use decisions must be endorsed.